Mindfulness-Based Cognitive Therapy for Procrastination (MBCT-P) to Reduce Muslim University Students’ Academic Procrastination: Mixed Methods Research - suhadianto, suhadianto; Hanurawan, Fattah; Eva, Nur; Rahmawati, Hetti (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study aimed to test the effectiveness of Mindfulness-Based Cognitive Therapy for Procrastination (MBCT-P) in reducing academic procrastination, as well as explain how MBCT-P can reduce academic procrastination. The research participants were 43 Muslim university students with academic procrastination scores in the medium and high categories who were randomly divided into the experimental group (n=21) and control group (n=22). A mixed methods research approach with an embedded research design was used in this study. An experiment with a Randomized Pre-Test and Post-Test Control Group with a Follow-Up design was used, while qualitative data collection was carried out during the intervention. The research instruments were the Tuckman Procrastination Scale (CR=0.89) and the Five Facet Mindfulness Questionnaire (CR=0.92). The results showed that MBCT-P had a long-term effect in reducing academic procrastination in the experimental group. Experimental group participants were reported to be more focused, calm, and motivated and found it easier to accept academic tasks, leading to reduced procrastination. The modification of MBCT-for depression for academic procrastination with a shorter duration has never been previously explored. Hence, this research provides a new alternative intervention that effectively reduces academic procrastination among university students.